Application of multi-indexing approach within a GIS framework to investigate the quality and contamination of ground water in Barisal sadar, Bangladesh - Md. Numan Hossain; M. Farhad Howladar; Sohag Ahammed; Md Rezwanul Haque; Majedul Islam Khan; Muyeed Hasan; Tayabur Rashid Chowdhury; Alamgir Hosain (Heliyon)
Groundwater quality and contamination pose significant challenges in coastal regions such as Barisal Sadar, Bangladesh, where dependency on groundwater is crucial for potable and agricultural uses. This study employed a multi-indexing approach inside a GIS framework to assess water quality, contamination scenarios, and health risks. It evaluates the physicochemical properties of groundwater samples, including heavy metals, to identify potential issues. The results reveal that water's pH is slightly alkaline, with moderate to high levels of turbidity and hardness. The mean electrical conductivity is 1522 μS/cm, and most regions are above the threshold value. Total dissolved solids (TDS), chloride, and NaCl were found in elevated amounts, indicating water's impact on salinity. Heavy metal concentrations occasionally exceed permissible limits, indicating potential health hazards. The individual contamination indices range from low to high risk, whereas the weighted index signifies low to medium risk. The possible ecological risk was obtained within acceptable ranges except for some samples. The noncarcinogenic health risk remained below acceptable ranges (<1) throughout this investigation. In some instances, the carcinogenic risk of Cd and Ni was more significant than the international safe limit (1E-04). The water quality index indicates that 55 % of samples are rated excellent, 10 % moderate, 15 % poor, and 20 % very poor. The significant positive correlations among EC, TDS, TH, turbidity, salinity, NaCl, chloride, and calcium ions as per correlogram, principal component analysis (PCA) biplot, and heat map clustering, indicating similar sources of origin. Notwithstanding its constraints, this study represented one of the initial attempts in Barishal Sadar to investigate groundwater using numerous indices and GIS frameworks. In the end, policymakers can utilize this study's findings to monitor and control groundwater around the study area.